Assessment of Tools for Marker-Assisted Selection in a Marine Commercial Species: Significant Association between MSTN-1 Gene Polymorphism and Growth Traits. (30th April 2012) - Sánchez-Ramos, Irma; Cross, Ismael; Mácha, Jaroslav; Martínez-Rodríguez, Gonzalo; Krylov, Vladimir; Rebordinos, Laureana
Abstract : Growth is a priority trait from the point of view of genetic improvement. Molecular markers linked to quantitative trait loci (QTL) have been regarded as useful for marker-assisted selection in complex traits as growth. Polymorphisms have been studied in five candidate genes influencing growth in gilthead seabream ( Sparus aurata ): the growth hormone ( GH ), insulin-like growth factor-1 ( IGF-1 ), myostatin ( MSTN-1 ), prolactin ( PRL ), and somatolactin ( SL ) genes. Specimens evaluated were from a commercial broodstock comprising 131 breeders (from which 36 males and 44 females contributed to the progeny). In all samples eleven gene fragments, covering more than 13, 000 bp, generated by PCR-RFLP, were analyzed; tests were made for significant associations between these markers and growth traits. ANOVA results showed a significant association between MSTN-1 gene polymorphism and growth traits. Pairwise tests revealed several RFLPs in the MSTN-1 gene with significant heterogeneity of genotypes among size groups. PRL and MSTN-1 genes presented linkage disequilibrium. The MSTN-1 gene was mapped in the centromeric region of a medium-size acrocentric chromosome pair.